Foreign nationality and age: A double drawback for reemployment in Germany? - Jana Bruder; Katharina Frosch (Universität Rostock, Institut für Volkswirtschaftslehre, 2006)
We analyze reemployment prospects for Germans and non-Germans over the life course. Older foreigners may experience a double drawback due to health issues, discrimination or differences in occupational structure. This effect might be alleviated by accumulation of country-specific skills over time and selectivity effects. We apply a piecewise-constant hazard rate model on more than 270.000 unemployment episodes drawn from the social insurance register for male employees aged 25 to 65 years between 1975 to 2001. Foreign nationality lowers reemployment prospects by 7 percentage points. On average, the effect of aging on reemployment is stronger for non-Germans. The effect of nationality differs strongly between nationalities and ranges from minus 17 percentage points for Greeks up to plus 5 percentage points for people from Ex-Yugoslavia. Aging is particularly a problem for foreigners from Greece and Turkey: Until age 60, their prospects for reemployment are, on average, about 27 percent below that of natives.
Keywords: J14; J15; J24; 330; labor migration; aging workforce; reemployment; proportional hazard rate models; demographic change